2007
DOI: 10.1093/treephys/27.2.261
|View full text |Cite
|
Sign up to set email alerts
|

Temperature responses of growth and wood anatomy in European beech saplings grown in different carbon dioxide concentrations

Abstract: Effects of temperature on growth and wood anatomy were studied in young European beech (Fagus sylvatica L.) grown in 7-l pots for 2.5 years in field-phytotron chambers supplied with an ambient (approximately 400 micromol mol-1) or elevated (approximately 700 micromol mol-1) carbon dioxide concentration ([CO2]). Temperatures in the chambers ranged in increments of 2 degrees C from -4 degrees C to +4 degrees C relative to the long-term mean monthly (day and night) air temperature in Berlin-Dahlem. Soil was not f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
32
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 32 publications
4
32
1
Order By: Relevance
“…Pronounced productivity stimulation by higher temperatures was found in various studies on beech (e.g. Piutti and Cescatti 1997;Bruhn et al 2000;Fotelli et al 2005;Saxe and Kerstiens 2005;Overdieck et al 2007). Our data show a productivity increase by about 60% with a 6°C-temperature increase (means of all treatments at 18 and 24°C) which matches well with the results of Overdieck et al (2007) who reported a 50% productivity increase in F. sylvatica saplings with a temperature increase by 4°C.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Pronounced productivity stimulation by higher temperatures was found in various studies on beech (e.g. Piutti and Cescatti 1997;Bruhn et al 2000;Fotelli et al 2005;Saxe and Kerstiens 2005;Overdieck et al 2007). Our data show a productivity increase by about 60% with a 6°C-temperature increase (means of all treatments at 18 and 24°C) which matches well with the results of Overdieck et al (2007) who reported a 50% productivity increase in F. sylvatica saplings with a temperature increase by 4°C.…”
Section: Discussionsupporting
confidence: 91%
“…Beech seedlings and saplings were studied in their response to elevated [CO 2 ] (e.g. Heath and Kerstiens 1997;Bruhn et al 2000;Kozovits et al 2005), elevated temperature (Leverenz et al 1999;Saxe and Kerstiens 2005;Overdieck et al 2007), low soil moisture (Madsen 1995;García-Plazaola and Becerril 2000;Fotelli et al 2001;Nielsen and Jørgensen 2003;Löf et al 2005) and increased N availability (Flückiger and Braun 1999;Finzi and Canham 2000;Thomas et al 2006). Most studies found significant growth responses to these factors.…”
Section: Introductionmentioning
confidence: 99%
“…Our findings showing an increased ray proportion with increasing site productivity indicate, contrarily to our initial hypothesis, for an absence of increased xylem carbon container with increasing stressful conditions and suggest that the xylem ray volume is rather linked to the growth ability of the tree, i.e., related with tree vigor and/or leaf area. However, ray abundance in response to elevated CO 2 concentration is contrasting, being negative in 20-year-old Scots pine (Kilpelainen et al 2007), unaffected in young Scots pine (Ziche and Overdieck 2004), and positive in European beech saplings (Overdieck et al 2007). Any significant difference in abundance of ray parenchyma has been found between different pine provenances from differently drought-exposed sites in Spain, although with differences in the proportion of ray tracheids, suggesting greater water storage capacity in the trunk of the more drought-exposed trees Martin et al 2010).…”
Section: Rays Per Tracheidmentioning
confidence: 99%
“…The wood from coppiced birch stands could replace, to a certain extent, Eucalyptus and other pulp wood often imported from far away (Peltola 2008), and the Russian birch pulp wood, the imports of which presumably ceases in the near future (Venäläisen puun … 2008). In addition, the warming climate, which is predicted to increase the growth of deciduous trees in the boreal zone (Kuusisto et al 1996), as well as the additional carbon in the atmosphere bound mainly in the aboveground growth (Overdieck et al 2007), may further enhance the future possibilities to grow downy birch in short rotations. Short-rotation cultivation, when based on coppicing, would also diminish the costs of regeneration and later management, also because early growth of birch coppices is faster than that of seedlings (Kauppi et al 1988, Hytönen andKaunisto 1999).…”
Section: Introductionmentioning
confidence: 99%